DESIGN OF A DIGITALIZED INDEPENDENT WASTE BANK INFORMATION SYSTEM USING GOOGLE APPS SCRIPT WITH AN INTEGRATED INPUT GATEWAY AND LIVE CALCULATOR - Fery Andika Kurniawan (Politeknik META Industri Cikarang, 2026)
Conventional waste bank management often faces challenges regarding transaction data recording accuracy, the risk of incorrect resident ID entry, and delays in updating savings balance information. This research aims to design and implement a digitized, web-based independent waste bank information system using Google Apps Script (GAS), Google Sheets as the database, and Bootstrap for the user interface. The design methodology focuses on minimizing human error by implementing a